Relatos de uma vivência interdisciplinar: educação, saúde e cidadania - Almeida Júnior, José Jailson de (2008)
This study addresses the interdisciplinary training in perspective for the Brazilian Health System (SUS) in view of graduation students in the areas of health of Federal University of Rio Grande do Norte s (UFRN) former students of the course Health and Citizenship (SACI). Emphasizes also the importance of commitment to social policies, particularly with those focused on the area of health. This is a case study with a qualitative approach. There was the lifting of data through documental research, from 14 portfolios of learning, which are weekly records of students from the respective discipline, corresponding to 2005.2 to 2007.2 semesters. From the analysis undertaken, inferred that the methodology problematizing, used by the discipline, enables students to understand that learning is not restricted to the confined university walls. It shows the health from a complex and concrete social reality, allowing students to an interdisciplinary dialogue in search of the transformation of this reality. It means an opportunity to interact with the dynamics of society in their area of activities, developing a relationship of solidarity in the formation of the citizen. Moreover, it was clear the direction of experienced interdisciplinary and recognized by students of various professions that make up the discipline. Thus, the SACI in preparation for construction of SUS, helps to form a new professional, more committed to the promotion and with a collective work in health